Experimental Study on Coal Permeability Variation during Microwave Radiation. (24th February 2020) - Ma, Yulin; Cheng, Yao; Shang, Wenlong; Zhao, Dong; Duan, Xianggang
Abstract : Coal-bed methane (CBM) is a new type of clean energy, which is abundant in China. Rational development and use of CBM can not only reduce the occurrence of mine disasters but also alleviate energy shortages. However, the "high storage capacity and low-permeability" characteristics of China's CBM have hindered the realization of industrialized CBM production. To study the effect of microwave radiation on the permeability of coal reservoirs, a seepage experiment under different stress and microwave radiation conditions was carried out by using the seepage experiment system of gas-bearing coal under microwave radiation developed by the authors. The relationship among different microwave powers, different irradiation times, different energy inputs, and coal permeability was explored. The results show that the microwave power effect and the temperature effect promote coal permeability. Under microwave radiation, the relationship between permeability and effective stress followed a negative exponential function, and all R-squared values were greater than 0.97. The permeability increased monotonically with increasing microwave power and irradiation time, and the linear fitting slope of the rate of increase in the low-effective-stress area was greater than in the high-effective-stress area. Under the same energy input, permeability increased with rising microwave power. The peak temperature of the coal sample also increased with increasing power. When the microwave power increased to a certain range, the permeability growth of the coal sample was the greatest, and the temperature gradient of the coal-sample temperature field was the steepest. The coal sample experienced the optimum microwave radiation power under the action of microwaves to achieve the permeability enhancement effect of microwaves on the coal sample. The experimental results provide a theoretical reference for applying microwave radiation technology in coal-bed methane extraction.